(untitled) (Journal of Economic Additions, 2025)
This study looks into social engineering as a significant security risk that takes advantage of human tendencies to get into systems without permission. Unlike hacking that targets technology, it uses psychology and social skills to influence people. The topic is seen as having two sides—it can be used for harmful actions like phishing and stealing identities, but it can also help build trust online and increase awareness about safety. A good response, according to the study, requires constant learning, enhanced cybersecurity tools, and a willingness to think carefully. It also points out that social engineering can be helpful when used wisely, by promoting ethics, improving digital skills, and running well-planned campaigns to spread the message. Keywords: Social Engineering, Society, Identity Theft, Vulnerabilities, Websites. Jel Classification Codes : D83، D91، L86 ، K24 ، O33.